2020
DOI: 10.1111/vco.12566
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant medical therapy provides no therapeutic benefit in the treatment of dogs with low‐grade mast cell tumours and early nodal metastasis undergoing surgery

Abstract: Lymph node (LN) metastasis is a negative prognostic factor in dogs with cutaneous mast cell tumors (cMCTs). While elective lymphadenectomy of metastatic LNs improves outcome, the benefit of adjuvant medical therapy in dogs with early metastatic (HN2) LNs is debated. The aim of this retrospective multicenter study was to evaluate the therapeutic benefit of adjuvant medical therapy following surgical removal of the primary low-grade cMCT (Patnaik grade 1-2 and Kiupel low-grade) and lymphadenectomy of HN2 LNs by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
78
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 40 publications
(82 citation statements)
references
References 22 publications
1
78
0
Order By: Relevance
“…This diagnostic procedure has an additional cost, but clinicians must advise the owner about the high percentage of occult metastatic SLN, and that lymphadenectomy seems to have not only a staging purpose but also a therapeutic value. 16,56 Another limiting aspect is the prolongation of anesthesiologic time due to the pre-operative lymphoscintigraphy, particularly in dogs with multiple tumors that have to be mapped and excised on the same day. After this case series, our surgical team decided to perform the pre-operative lymphoscintigraphy the day before surgery, to reduce the anesthesiologic time.…”
Section: Discussionmentioning
confidence: 99%
“…This diagnostic procedure has an additional cost, but clinicians must advise the owner about the high percentage of occult metastatic SLN, and that lymphadenectomy seems to have not only a staging purpose but also a therapeutic value. 16,56 Another limiting aspect is the prolongation of anesthesiologic time due to the pre-operative lymphoscintigraphy, particularly in dogs with multiple tumors that have to be mapped and excised on the same day. After this case series, our surgical team decided to perform the pre-operative lymphoscintigraphy the day before surgery, to reduce the anesthesiologic time.…”
Section: Discussionmentioning
confidence: 99%
“…It may thus be argued that for tumors smaller than 3 cm, SLN mapping and biopsy could be avoided; however, it should be underscored that the discriminant ability of tumor size remains moderate. According to the current veterinary literature, the removal of HN2 lymph nodes has a potential therapeutic effect and should thus be performed anyway [ 29 , 30 ]. Further studies comparing the outcome of dogs with tumors smaller than 3 cm admitted or not to SLN biopsy are needed to confirm the unnecessary nature of the procedure in these cases.…”
Section: Discussionmentioning
confidence: 99%
“…The final decision to perform the sentinel lymph node mapping and biopsy should take into account the association with the nodal staging (as tested in the present study) and the benefit of such procedures on the oncological outcome. As previously cited, recent papers on RLN reported a possible therapeutic effect of lymphadenectomy in the presence of early metastasis in canine MCT, although data on SLN are lacking [ 29 , 30 ]. In the study population, only 3 out of 53 dogs had an MCT relapse at a median follow-up time of 455 days (range, 15–1305 days) (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, both systems are frequently used in routine diagnostic and clinical practice and are included in the most recent publications on the epidemiology, prognosis, and treatment of canine cutaneous MCTs. 66,91,104 Relevantly, studies on MCT grading system should avoid mixing cutaneous MCTs and primarily subcutaneous MCTs. Subcutaneous MCTs are less common than their cutaneous counterparts with less information in the literature regarding their histologic diagnosis and biologic behavior, although some authors have suggested a favorable clinical outcome when arising in the subcutaneous tissue.…”
Section: Canine Mast Cell Tumorsmentioning
confidence: 99%